Analysis of Village Government Financial Performance Using the Value for Money Method in Pamenang District, Merangin - Nur Rahmi; Sri Rahayu; Salman Jumaili (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the financial performance of village governments in Pamenang District, Merangin Regency using the value for money method which measures economic ratios, efficiency ratios and effectiveness ratios. This research is quantitative descriptive. The data used in this research is secondary data with documentation techniques. This research was conducted in 13 villages in Pamenang District, Merangin Regency. The results showed that the financial performance of the Village Government in Pamenang District, Merangin Regency, seen from the average economic ratio, was categorized as quite economical, seen from the efficiency ratio, it was categorized as efficient and the effectiveness ratio was categorized as quite effective